2023
DOI: 10.5334/aogh.3891
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Training in Emergency Obstetric Care in Sub-Saharan and Central Africa: A Scoping Review

Anne A. C. Van Tetering,
Peter Ntuyo,
Renata P. J. Martens
et al.

Abstract: Background: Every day approximately 810 women die from complications related to pregnancy and childbirth worldwide. Around two thirds of these deaths happen in sub-Saharan Africa. One of the strategies to decrease these numbers is improving the quality of care by emergency obstetric simulation-based training. The effectiveness of such training programs depends on the program’s instructional design. Objective: This review gives an overview of studies about emergency obstetric simulation-based training and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The successful transfer of the program from FCD to Addis Ababa University CDT-Africa facilitated country ownership and positioned the local partner institution as a sustainable LMIC training hub. Previous studies on training initiatives for health professionals in Africa have shown the potential to improve competency and performance[30][31][32][33][34], yet there is limited information on competency in clinical trial capacity. The program's success in enhancing participants' pro ciency in clinical trials was notably marked by a signi cant improvement.…”
mentioning
confidence: 99%
“…The successful transfer of the program from FCD to Addis Ababa University CDT-Africa facilitated country ownership and positioned the local partner institution as a sustainable LMIC training hub. Previous studies on training initiatives for health professionals in Africa have shown the potential to improve competency and performance[30][31][32][33][34], yet there is limited information on competency in clinical trial capacity. The program's success in enhancing participants' pro ciency in clinical trials was notably marked by a signi cant improvement.…”
mentioning
confidence: 99%